Institutional isomorphism on environmental reporting practices in Malaysian local governments / Che Ku Hisam Che Ku Kassim …[et al.] - Mohd Nasir, Noor Emilina; Ahmad, Suraya; Wan Mohd Nori, Wan Mohd Nazif; Mod Arifin, Nur Nariza; Che Ku Kassim, Che Ku Hisam (Universiti Teknologi MARA, 2021)
The extent of environmental disclosures (EDs) supplied by local governments (LGs) is gradually on the rise despite a lack of mandatory reporting regulations. Studies have predominantly relied on the sociopolitical theories to examine the underlying motives behind the disclosure. Little has been researched on the environmental reporting (ER) practices of the LGs from the lens of the Institutional Theory. Therefore, the main objective of the paper was to examine the institutional isomorphism that may have influenced ER practices in Malaysian LGs. A triangulation of methods consisting of a descriptive content analysis and a self-administered questionnaire survey were employed to measure the extent of EDs and to elicit the influential institutional isomorphism on the LGs’ reporting practices respectively. The multiple regressions indicated that normative isomorphism in the form of continuous professional development poses a significant pressure for LGs to engage in ER practices. The results suggest that a change in public policy to mandate the EDs is inevitable to further enhance the quantity and quality of EDs reported by the Malaysian LGs.